Kerangka Konseptual Kepuasan Pelanggan terhadap Jasa Transportasi Online Go Ride menggunakan Service Quality - Hawwin Mardhiana (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2019)
Customer satisfaction in organizations is one of the critical succes factors for developing organizations. To improve the quality of services, an organization must know customer satisfaction with the services provided by the organization. This study aims to present a conceptual framework that is used to analyze factors that affect service quality, customer loyalty and intention to repurchase or reuse online transportation services, Go-Ride. A conceptual framework proposed to measure Go-Ride customer satisfaction and its impact on customer loyalty and intention to repurchase. Starting from analyzing what is expected and what is felt by customer when the customer use these services with Servqual Method. This conceptual framework allows stakeholders in online transportation Go-Ride to understand customer and measure the quality of services. Conceptual Framework also can be used to set strategy and decision making improve the quality of customer services. In this study the transportation service provider can also divide customers into various categories, so the organization know how to position itself in the future that can be compared to quality of service with the competitors.Keywords : Go-Ride, Servqual, Customer Satisfaction, Servqual, Customer Loyalty, Intention to repurchase